2021
DOI: 10.1038/s41467-021-24710-8
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to brain epigenetic analysis reveals kinases associated with Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is influenced by both genetic and environmental factors; thus, brain epigenomic alterations may provide insights into AD pathogenesis. Multiple array-based Epigenome-Wide Association Studies (EWASs) have identified robust brain methylation changes in AD; however, array-based assays only test about 2% of all CpG sites in the genome. Here, we develop EWASplus, a computational method that uses a supervised machine learning strategy to extend EWAS coverage to the entire genome. Application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 73 publications
(93 reference statements)
1
29
0
Order By: Relevance
“…RBFOX1 (SNP: rs55642412, CorrectedP: 3.18755E-23) has been found to play a role in neuronal development ( Raghavan et al, 2020 ). PTPRD (SNP: rs62538998, CorrectedP: 1.92988E-19) has been confirmed to be related to AD and MCI in previous studies ( Huang et al, 2021 ). DLGAP2 (SNP: rs72507619, CorrectedP: 3.74049E-17) was found to be predominantly expressed in the brain and associated with a wide variety of neurological disorders ( Linthorst et al, 2020 ).…”
Section: Resultssupporting
confidence: 58%
“…RBFOX1 (SNP: rs55642412, CorrectedP: 3.18755E-23) has been found to play a role in neuronal development ( Raghavan et al, 2020 ). PTPRD (SNP: rs62538998, CorrectedP: 1.92988E-19) has been confirmed to be related to AD and MCI in previous studies ( Huang et al, 2021 ). DLGAP2 (SNP: rs72507619, CorrectedP: 3.74049E-17) was found to be predominantly expressed in the brain and associated with a wide variety of neurological disorders ( Linthorst et al, 2020 ).…”
Section: Resultssupporting
confidence: 58%
“…To date, 19 blood-based biomarkers have been chosen for further study towards the diagnosis of Alzheimer’s disease [ 93 ]. Recently, Huang Y et al created Epigenome-Wide Association Studies (EWAS) plus, a computational technique that employs a supervised machine learning strategy, to expand the coverage of multiple EWASs to the entire genome rather than only about 2% of all CpG sites in the genome [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no prior study has reported on AD detection based on cfDNA. However, a study using brain epigenetic analysis identified kinases associated with AD [ 48 ]. DNA methylation analysis based on brain tissue [ 49 ] has achieved good predictive accuracy with an AUC of >0.79 [ 50 ] but not an excellent predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem brain tissue was used to generate CpG methylation data using the Illumina-450 array. These traits were beta-amyloid accumulation, neurofibrillary tangles (NFTs), Braak staging, Consortium to establish a Registry of Alzheimer’s Disease (CERAD) score, global pathology and cognitive trajectory study using epigenetic analysis of brain tissue [ 48 ]. CpG methylation had AUCs = 0.850−0.962 for trait detection.…”
Section: Discussionmentioning
confidence: 99%